Craniofacial anthropometry of major ethnic groups of Sabah - Zainal Ariffin Mustapha; Daw Khin Saw Naing; Sharifah Norhafizah S. Abd. Hamid (Universiti Malaysia Sabah, 2014)
Craniofadal anthropometry is a measurement of skull and face. It can be defined by size and shape, and both are analyzed. Quantitatively determining the extent of deviation of an individual's fadal pattern from the normal state requires the collection of data on normal individuals in order to establish numerical descriptions of normal measurement ranges. Several studies showed anthropometric differences between racial groups. The objectives of this study is to compare craniofacial norms and proportions among Rungus ethni and Bajau ethnic group in Sabah, their relation to divine proportion, cephalic index(O) and prosopic index(PI) of both ethnic groups. A total of 400 subjects of Bajau and Rungus have been recruited for this study. The measurements were obtained by using martin breadth spreading caliper and measuring tape. 25 linear measurements were taken twice from 22 landmarks from six craniofacial regions and were marked on the skin using eyeliner. In Rungus ethni, the obvious different measurement contributed to significantly different result (p value<0.05), except for width of the head (eu-eu), length of the head (g-op), forehead height I (tr-g), forehead height II (tr-n), and protrusion of nasal (sn-pm) for both respective gender and the higher measurement were found in Rungus males. Bajau males and females established significantly difference (p value<0.05) in the measurement of the distance from the top of the head to lower border of chin (v-gn), special forehead height (v-en), height of calva (v-tr), special face height (en-gn), special upper face height (g-sn), face height (n-gn), lower face height (sn-gn), facial width I (zy-zy), facial width II, eye fissure width( ex- en), binocular width (ex-ex),nose length (n-sn), nose width (al-al), protruSion of nasal (sn-prn), alar length (acpm), mouth width (ch-ch), upper lips height (sn-sto) and ear length in both gender. In comparison of both ethnic groups, the width of head (eu-eu), the length of head (g-op), the distance from the top of head to lower border of chin (v-gn), special forehead height(v-en), height of calva (v-tr), special face height (en-gn), special upper face height (g-sn), lower face height (sn-gn), fadal width I (zy-zy), facial width II, eye-fissure width(ex-en), biocular width (ex-ex), protrusion of nasal ( sn-pm), alar length (ac-pm) and ear length (sa-sba) can be used to differentiate a Rungus face from a Bajau. Both ethnic groups had proportion more than 1.618 which not considered as ideal facial proportion. The mean cephalic index in males Rungus was 62.7 and females Rungus was 61.5 respectively. While in Bajau ethnic group, their mean of cephalic index in males was 50.9 and 49.4 in females. Hence, it showed that both Rungus and Bajau had dominance of dolichocephalic phenotype in both sexes. In relation to prosopic index, the mean of prosopic index of Rungus males is 74.3 and Rungus females is 72.2 respectively while Bajau males had the mean of cephalic index of 74.2 and females with the mean of cephalic index of 70.6 respectively. Both ethnic groups belong to hypereuriprosopic fadal shape. As conclusion, statistical analysis proved that there was significantly different in certain parameter of craniofadal norms for both gender in Rungus and Bajau ethnic groups. Both ethnic groups also do not follow the divine proportion whereas their proportion is more than 1.618. Most of Rungus and Bajau also were found to have dolicocephalic head shape and hypereuriprosopic facial shape. However, there was no significant different found in both of ethnic groups when comparing their cephalic index and prosopic index (P value >0.05).